Hubungan Antara Dukungan Sosial dengan Subjective Well-Being pada Mahasiswa Program Studi Psikologi di Universitas Sahid Surakarta - Sri Hartini; Sri Ernawati; Faqih Purnomosidi (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2025)
Social support is assistance to individuals in the form of comfort and attention as well as created a feeling of being loved and appreciated by others. Social support of individuals will be able to fulfill one of the psychological needs positively. This can affect subjective well-being in individuals. This study aims to determine and empirically test the correlation between social support and subjective well-being in students of the Psychology Study Program at Sahid Surakarta University. This study used a quantitative method with 67 students as respondents. The sampling technique used a purposive sampling technique. The results indicate that there is a correlation between social support and subjective well-being in psychology students at Sahid Surakarta University. This means that higher social support contributes to the higher subjective well-being of students. In contrast, the lower social support makes for the lower subjective well-being of students.